2020
DOI: 10.1177/1049731520958489
|View full text |Cite
|
Sign up to set email alerts
|

Examining a Child Welfare Parenting Intervention for Parents With Intellectual Disabilities

Abstract: Purpose: There is scant child welfare research on parenting interventions for parents with intellectual and developmental disabilities (I/DD). This mixed-methods research examined client participation in an in-home parenting intervention, including client characteristics, which clients benefit most from participation, and key aspects of program participation. Method: The sample included participant program records, client satisfaction surveys, stakeholder interviews, and a staff focus group. The quantitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Research confirms that parents with intellectual disabilities, similar to nondisabled fathers involved in the child welfare system, can effectively use programs aimed at strengthening their life and parenting competences, which can significantly contribute to reducing cases of limiting their rights (Augsberger et al, 2021; English et al, 2009). Further analyses focused on positive phenomena illustrating the fathers' resources and the ability to use them in the implementation of life roles (including family and professional) would be of value in future studies.…”
Section: Discussionmentioning
confidence: 84%
“…Research confirms that parents with intellectual disabilities, similar to nondisabled fathers involved in the child welfare system, can effectively use programs aimed at strengthening their life and parenting competences, which can significantly contribute to reducing cases of limiting their rights (Augsberger et al, 2021; English et al, 2009). Further analyses focused on positive phenomena illustrating the fathers' resources and the ability to use them in the implementation of life roles (including family and professional) would be of value in future studies.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Ćwirynkało and Parchomiuk (2024) explored the lived experiences of fathers with intellectual disabilities when interacting with child protective services in Poland. Consistent with the use of diverse social supports used by fathers in the Ćwirynkało and Parchomiuk (2024) study, Augsberger et al (2021) suggested additional supports of persons with disabilities to include access to parenting programs and comprehensive services to address risk factors while promoting the parental strengths. Authors offered resources, practical implications, and translated the findings to specific recommendations.…”
Section: Hope Happiness and Healthmentioning
confidence: 90%
“…Therefore, it could be possible that the parents of these Lac may have fallen under the diagnostic radar and been misdiagnosed or even missed altogether as the need to treat other conditions may have overridden-more in-depth exploration of potential NDDs. Particularly, if we take into account that parents of Lac often have challenges in areas of mental health, substance misuse, domestic abuse and learning di culties or disabilities which may be masking the characteristics of a ND (100,101). The higher prevalence rates as already discussed require further investigation to ensure that the children/young adults who have been placed in the care system receive the most up to date specialist, holistic therapeutic interventions to enable them to ourish within society and attain positive health and social outcomes.…”
Section: Prevalence Of Nddsmentioning
confidence: 99%